Peluang dan Tantangan Penerapan Cyber Notary di Indonesia - Mega Meilani Reformisiane (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the challenges and opportunities for implementing Cyber ​​Notary in Indonesia using normative juridical legal research methods. This study uses various legal materials that produce new arguments and concepts. The results of this study analyze various challenges and opportunities for implementing Cyber ​​Security in Indonesia by looking at the Notary Law and Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions. It also analyzes whether it is possible to digitize authentic deeds that initially required physical presence to digital signatures and fingerprints. Notaries can utilize digital applications to store, manage, and validate documents electronically. This can increase productivity and reduce operational costs. Therefore, the implementation of Cyber ​​Notary in Indonesia can support an effective and efficient public service process. To take advantage of some of the opportunities described above, a collaborative process or effort is needed between the government, notary associations, and other stakeholders. One of these is through education and socialization regarding Cyber ​​Notary to build public trust. Furthermore, there are concerns regarding data security and the overall reach of Cyber ​​Notary in Indonesia. The results of this study are crucial for supporting the gradual implementation of Cyber ​​Notary in Indonesia.